(untitled) (Third Sector Social Economic Review, 2023)
Civil servants, workers, retirees, self-employed people whose earnings are determined by annual tariffs, and landlords who rent out their houses, can buy less goods and services with the same amount of money every month, compared to the previous month, with the effect of the constant increases in the general level of prices. This group, which is defined as fixed income earners, can realize their losses more clearly and in a short time in a high inflation environment, but they can feel it after 3-4 months in a low inflation environment. Inflation, depending on the rate, melts the earnings of fixed incomes like the teeth of a saw. Although the increases in the earnings of this group in annual or semi-annual periods seem to eliminate the melting in incomes, it is revealed by the study that the reality is not so. In this study, calculations were made on the basis of different occupations and income groups of fixed incomes in the inflation environment. In the calculations, it was found that the annual or semi-annual inflation caused losses from its earnings in the period until a new increase in earnings. The results show that, while the earnings of fixed incomes have been decreasing continuously, their share in GDP has been decreasing continuously in the last 7 years at rates varying according to the sectors. This study shows that the rhetoric that ""fixed income earners are not crushed by inflation"" does not reflect the truth, as the annual or semi-annual increases in the inflation rate to the earnings of fixed income earners in an inflationary environment.